The effects of SOST on implant osseointegration in ovariectomy osteoporotic mice. (February 2017) - Shu, Rui; Ai, Dongqing; Bai, Ding; Song, Jinlin; Zhao, Mengyuan; Han, Xianglong
Highlights: Osteoporosis mouse model was successfully established by ovariectomy surgery. SOST deficiency ameliorates the bone loss induced by ovariectomy surgery. SOST deficiency improves the osteointegration of implant in both normal and osteoporosis mice. Abstract: Objective: Osteoporosis is a risk factor for implant fixation failure. The inhibition of sclerostin effectively improves bone formation and bone remodeling. Therefore, this study investigated whether SOST deficiency enhances the osseointegration of implants in a mouse model of osteoporosis induced by ovariectomy (OVX). Design: Osteoporosis was induced in female C57BL/6 and SOST deficient mice by OVX. Titanium implants were placed in the bilateral distal aspects of the femurs. Implants underwent sandblasting and acid-etching after which the structure, surface roughness and chemical components were investigated using scanning electron microscopy (SEM) and energy spectrum analyses. Undecalcified slices, μ-CT, histology analyses and mechanical tests were used to evaluate the osseointegration of implants. The results were compared using one-way ANOVA between four groups. Results: Sandblasting and acid-etching increased the roughness of the implants. OVX surgery reduced bone formation around the implants in both WT and SOST −/− mice. However, implant osseointegration was significantly improved in the SOST −/− OVX mice compared to the WT OVX mice. Conclusions: Inhibition of the SOST gene improved implant fixation in the OVX osteoporotic mice, which suggests a strategy for enhancing implant osseointegration in clinical patients with osteoporosis.